Increased Level of IFN-γ and IL-4 Spot-Forming Cells on ELISPOT Assay as Biomarkers for Acute Graft-Versus-Host Disease and Concurrent Infections - Hirayama, Masahiro (MDPI, 2012)
Acute graft-versus-host disease (aGVHD) remains a significant cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation. Infections may coexist and in certain circumstances aggravate aGVHD. It was described that type 1 as well as type 2 cytokines are important mediators of aGVHD. We measured spot-forming cells (SFCs) for interferon (IFN)-γ, interleukin (IL)-4, IL-10, and IL-17 in unstimulated peripheral blood from 80 patients with hematological disorders who underwent allogeneic hematopoietic stem cell transplantation by using the enzyme-linked immunospot (ELISPOT) assay that reflects the ongoing in vivo immune status. A serial monitoring showed that both type 1 and type 2 cytokine SFCs were correlated with aGVHD activity. The numbers of IFN-γ and IL-4 SFCs in patients with grade II-IV aGVHD were significantly higher than those in patients with grade 0 and/or I aGVHD. Elevation of IFN-γ and IL-4 SFCs was significantly correlated with the severity of aGVHD, but not with infection itself, e.g., cytomegalovirus infection. Cytokine SFCs are clinically relevant biomarkers for the diagnostic and therapeutic evaluation of aGVHD and concurrent infection.